Agon-Are Military Officers Educated for Modern Society? - Leif Inge Magnussen; Ole Boe; Glenn-Egil Torgersen (MDPI AG, 2023)
The research question in this article concerns how a competitive environment affects the learner's (officer cadet's) personal leadership development and their relationship to their team and with future civilian foundations. More specifically, what are the possible learning effects of the 'hidden' curriculum? This article investigates how more than 250 years of leadership education provides new army officers with new skills and how this environment may affect the cadets' leadership training. The article builds on ethnographic data gathered during the three-year education programme in most of the relevant practical locations and contexts. Data were collected using both interviews and a questionnaire. Regarding trust in their learning environment, cadets reported a mean score of 2.83 on a 1 (low trust) to 5 (high trust) Likert scale, underpinning interview data regarding the lack of trust in the Norwegian Military Academy (NMA) and in their fellow cadets. Cadets also pointed out that competition hindered their learning (mean = 2.50). These findings are interpreted in relation to possible negative effects stemming from internal competition and the evaluation system as a whole. The overall output of this system is a zero-sum game, and thus affects evaluative practices and learning processes. This study is of relevance to higher education officers responsible for designing learning environments.